The Influence of Warm Compress and Progressive Muscle Relaxation Therapy in Decreasing Joint Pain to Elderly at Posyandu Lansia RW 04 Kelurahan Bangsal Kota Kediri - Selvia David Richard; Dyah Ayu Kartika Wulan Sari (Journal of Innovation and Applied Technology, 2020)
Pain management does not always have to use drugs, but there are some nursing measures that can be given to relieve pain such as relaxation therapy, for example TROP and warm compress. The study population was all elderly who experienced joint pain. The samples were 36 respondents, which were divided into two intervention groups. Sampling method used purposive sampling technique. Data collected by using Numerical Rating Scale (NRS). Data were analyzed using Wilcoxon signed ranks test with α = 0.05. The conclusion of this study is TROP and warm compresses can be used to reduce joint pain scale in the elderly, although statistically shows that TROP intervention is more effective in reducing pain.